Improving English Speaking Abilities by Using Mafia Games - Firmayanti, Putri Wahyu; Adi, A B Prabowo Kusumo; Lestari, Maria Yosephin Widarti (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aimed to enhance students' speaking abilities using Mafia Games in a classroom setting. The research involved 9 students in DCT-1 class at BBC Banyumanik Semarang. Data was collected through observation sheets, measurement tests, and open-ended questionnaires. This research employs a Classroom Action Research (CAR) design and is conducted in two cycles during mid-term and final-term. Results showed an improvement in communication/content from 66 to 85, pronunciation from 68 to 84, range of vocabulary from 67 to 86, and grammar/accuracy from 65 to 86 between the first and second cycles which passed the BBC's Minimum Completeness Criteria of 70 points. The finding showed that the Mafia Games make learning activities more enjoyable and students are able to speak more confident through the game that marked by increased the BBCs’ speaking measurement points.